INTEGRATION OF DISCOVERY LEARNING MODEL, LOCAL CULTURAL CHARACTER SASAMBO, AND PROBLEM-SOLVING SKILLS IN TEACHING BASIC SCIENCE CONCEPTS: A LITERATURE REVIEW - Ibrahim; Bahtiar; Maimun; Ni Made Yeni Suranti; Nurkhaerat Alimuddin; Yuliana, Ina (Jurnal Pendidikan Fisika Undiksha, 2024)
This research aims to conduct a literature review on the integration of the Discovery Learning Model, SASAMBO Local Cultural Character, and problem solving skills in teaching basic science concepts at the elementary level. The research method used in this study involves a literature review analysis of relevant scientific articles selected based on certain criteria relevant to the objectives of this research. In this literature review, researchers analyzed five relevant scientific articles that discuss this approach. The results of the literature review show that the integration of the Discovery Learning Model in science learning is effective in increasing student involvement, stimulating interest in learning, and deepening understanding of scientific concepts. Apart from that, the integration of SASAMBO's Local Cultural Character also has a positive impact by increasing students' relevance and motivation towards science learning. The integration of problem-solving skills also helps students develop important critical, analytical, and creative skills. Nonetheless, challenges in implementing this integration, such as teacher training and sensitivity to students' cultural context, need to be addressed through continued research and collaboration between educational stakeholders. By optimizing the implementation of this integration, it is hoped that it can create a dynamic and inclusive learning environment, which empowers students to achieve success in science and their future lives.